Knowledge Management Capabilities and SMES Performance in Computer Village Ikeja, Lagos - Udeh Prisca Chinecherem (Rowter Journal, 2026)
In today’s knowledge-driven economy, effective management of knowledge resources is critical for the competitiveness and sustainability of small and medium-sized enterprises (SMEs). Despite SMEs’ significant contributions to employment and economic development, particularly in Nigeria, many still face constraints such as inadequate infrastructure, limited technology adoption, and informal knowledge-sharing practices. This study investigates the relationship between knowledge management capabilities—comprising knowledge acquisition, application, storage, and creation—and SME performance within the dynamic context of Computer Village, Ikeja, Lagos. Employing a quantitative survey research design, data were collected from 375 SMEs using structured questionnaires and analyzed through descriptive and regression analyses. The results demonstrate that all four dimensions of knowledge management significantly and positively impact SMEs’ performance, influencing areas such as innovation, operational efficiency, and customer satisfaction. Findings highlight the importance of structured knowledge practices over informal methods to prevent knowledge loss and enhance competitive advantage. The study recommends that SMEs invest in digital tools for knowledge storage, cultivate cultures that encourage sharing and innovation, and leverage external collaborations to enrich knowledge bases. These insights are crucial for business owners, policymakers, and stakeholders aiming to harness knowledge as a strategic asset to drive sustainable growth and resilience in Nigeria’s SME sector.